2017
DOI: 10.1016/j.ejor.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion in imperfect natural gas markets

Abstract: This paper presents a natural gas market equilibrium model that considers uncertainty in shale gas reserve exploration. Risk aversion is modeled using a risk measure known as the Average Value-at-Risk (also referred to as the Conditional Value-at-Risk). In the context of the European natural gas market, we show how risk aversion affects investment behavior of a Polish and a Ukrainian natural gas supplier. As expected, increased risk aversion leads generally to lower investment, and a larger share of investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A natural gas market equilibrium model considering risk aversion related to uncertainty in shale gas reserve exploration is proposed by Egging et al. (). Three types of agents are considered: suppliers (who take risks), a transmission operator, and consumers.…”
Section: Energymentioning
confidence: 99%
“…A natural gas market equilibrium model considering risk aversion related to uncertainty in shale gas reserve exploration is proposed by Egging et al. (). Three types of agents are considered: suppliers (who take risks), a transmission operator, and consumers.…”
Section: Energymentioning
confidence: 99%
“…Nwaoha et al [40] indicated a decline in the production of oil, but growth in the utilization of natural gas globally. However, production dropped by 1.7% in Europe and Eurasia [41]. Though domestic natural-gas production is decreasing in Europe, consumption has increased with a higher number of imports, making it 15.3% of the total global consumption in 2011 [42].…”
Section: Countrymentioning
confidence: 99%
“…Let also say that P n ⊆ P, C n ⊆ C are located in node n ∈ N. Let A n be the pipelines connected to node n. The symbols used here are explained in Table 1, 2 and 3. Most of the analysis closely follow [18] and [14]. Random parameters are denoted by an (ω) beside them.…”
Section: Natural Gas Market -Complementarity Formulationmentioning
confidence: 99%
“…The behavior of a solution to a complementarity problem with random parameters was first addressed in [25], where such problems were referred to as stochastic complementarity problems (SCP). Authors in [9,14,23,30,42] define various formulations of SCP for different applications and have devised algorithms to solve the problem. Authors in [35] compute confidence intervals for solution of the expected value formulation of the problem, however they do not have efficient methods to find the second-order statistics for large-scale complementarity problems.…”
Section: Introductionmentioning
confidence: 99%